The brain and fatigue: New opportunities for nutritional interventions? - Meeusen, R.; Watson, P.; Dvorak, J. (Journal of Sports Sciences, 2006)
It is clear that the cause of fatigue is complex, influenced by events occurring in both the periphery and the central nervous system. Work conducted over the last 20 years has focused on the role of brain serotonin and catecholamines in the development of fatigue, and the possibility that manipulation of neurotransmitter precursors may delay the onset of fatigue. While there is some evidence that branched-chain amino acid and tyrosine ingestion can influence perceived exertion and some measures of mental performance, the results of several apparently well-controlled laboratory studies have not demonstrated a positive effect on exercise capacity or performance under temperate conditions. As football is highly reliant upon the successful execution of motor skills and tactics, the possibility that amino acid ingestion may help to attenuate a loss in cognitive function during the later stages of a game would be desirable, even in the absence of no apparent benefit to physical performance. There are several reports of enhanced performance of high-intensity intermittent exercise with carbohydrate ingestion, but at present it is difficult to separate the peripheral effects from any potential impact on the central nervous system. The possibility that changes in central neurotransmission play a role in the aetiology of fatigue when exercise is performed in high ambient temperatures has recently been examined, although the significance of this in relation to the pattern of activity associated with football has yet to be determined.